A Comparison QoS Indihome in Tangerang and Palu (International Journal of Applied Research and Innovation, 2026)
This study investigates the Quality of Service performance of IndiHome internet services in Tangerang and Palu, Indonesia, through a comparative empirical evaluation. The research integrates bandwidth assessment with multidimensional Quality of Service measurements to examine network performance under comparable operational conditions. Data were collected using Wireshark and NetWorx during controlled streaming activities employing identical content, service providers, and observation periods. The evaluated parameters included delay, jitter, packet loss, throughput, and bandwidth utilization. The findings reveal notable differences between the two locations. Tangerang exhibited superior performance in terms of delay and jitter, indicating better network responsiveness and transmission stability. Palu achieved higher throughput values, demonstrating stronger data transfer capacity under the observed conditions. Both locations recorded zero packet loss, reflecting reliable packet delivery and stable communication quality. The results indicate that throughput should not be interpreted independently because overall service quality is influenced by the interaction among latency characteristics, resource utilization efficiency, traffic management, and infrastructure conditions. The study further highlights the importance of network architecture effectiveness and bandwidth optimization in maintaining broadband service quality. These findings provide practical insights for infrastructure planning, service improvement, and digital connectivity development across geographically diverse regions